Understanding the inclination of South Indian nursing graduates in using mobile learning applications - Cynthia Milton; Aruna Subramaniam (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Clinical-based mobile learning courses have great demand among the nursing graduates as learners look for possibilities to update skills. The present study explores the feasibility, familiarity, utility, and attitude of nursing graduates of South India toward mobile learning applications (m-apps). MATERIAL AND METHODS: An online-based cross-sectional descriptive survey was conducted in May 2021 among the South Indian nursing graduates of Tamil Nadu and Kerala, using a questionnaire consisting 49 items categorized under six sections with items related to socio-demographic information; m-app usage; online learning experience; preference in using m-apps for learning purposes before COVID-19 and during COVID-19; students' engagement through e-learning; and anxiety related to online assessment. Descriptive and inferential (ANOVA, Chi-square, and t test) statistical data analysis were done using SPSS version 23. RESULTS: A total of 447 student nurses responded. The result shows that most of them, 96% (432) used android phones and 94% (422) owned a mobile. Age was highly influencing mobile learning application (m-learning apps) usage; students of less than 20 years of age used applications more frequently and possessed more educational applications. Majority of them, 84% (377) of them had started using m-learning apps only after COVID. 57.7% (249) commonly used m-learning apps for acquiring nursing knowledge resources, nursing exam preparatory, and drug resources. Students rated high for the interactive nature of these m-learning apps, while abundant learning materials and usage with ease were rated as other attractive features. Sixty-six percent (305) had mostly downloaded these apps from Google Play Store. CONCLUSION: The findings would help the m-learning application developers to offer customize solutions to address learning gaps that prevail among the South Indian nursing graduates and help with sustainable growth.